Weight status as a predictor for microalbuminuria among the Samarahan district rural community in Sarawak - Than, T. A; Zulkarnaen, M; Razitasham, S.; Md Mizanur, Rahman; Ahadon M, Ahadon M; Arlizan, B.A; Dayangku Norlida, A.O (2021)
Introduction: Obesity and chronic kidney disease (CKD) have emerged as important public health problems. Microalbuminuria is a known early predictive factor for renal disease. This study aimed to determine the association between weight status and microalbuminuria among the rural adult community in Sarawak. Materials & Methods: A cross-sectional study was carried out among 610 subjects. A pre-tested questionnaire was used for social demographics, personal lifestyle and family history of CKD. The urine dipstick examination was used for detection of microalbuminuria and a measurement of 20 mg/L or above was considered as positive for microalbuminuria. Body mass index (BMI) was classified according to the Ministry of Health Malaysia criteria. Logistic regression analysis was performed to evaluate the relationship between the presence of microalbuminuria and BMI. Results: One-fourth (26.9%) of the rural adult population had microalbuminuria. A hierarchical binary logistic regression analysis revealed that BMI status of underweight (Adj. OR= 4.072, 95% CI=1.334, 12.427) and obese (Adj. OR= 2.715, 95% CI=1.492, 4.942) appeared to be important predictors of microalbuminuria. However, age, and gender had no association with microalbuminuria (p>0.05). Discussion: Among the studied subjects, 26.9% had microalbuminuria. Microalbuminuria in a rural adult community in Sarawak was associated with BMI status of underweight and obese in both men and women. We recommend further research to shed more light on the association between underweight and microalbuminuria among the high risk group in this community